The relationship between information technology skills and competencies on junior accounting graduates employability / Nur Nadiah Saiman - Saiman, Nur Nadiah (2022)
This research discovers IT skills and competencies for accounting graduates which are essential for them to work competently in the industry at the early stage after graduation. In line with the evolvement in technology, it has crucial for accounting graduates to acquire and master accounting related to IT skills and competencies for them to be resourceful, ranging from their first day in the profession. There is consequently growing concern about the level of IT skills and competencies that accountants possess in the use of information technologies, as well as whether they are equipped to handle the challenges of the modern business environment. The skills that professional accountants have acquired, however, are still below the minimum standard set by accounting professional bodies like the Malaysian Institute of Accountancy (MIA). Therefore, this study focuses on the relationship between IT skills and competencies among junior accounting graduates’ employability. A quantitative research method through drop-and-collect questionnaires was distributed by MIA. A total of 341 questionnaires were sent out. However, only 240 of the 341 completed questionnaires were selected for the study because the respondents selected were below the age of 30. Descriptive findings reveal that IT skills and competencies in office automation skills, IT knowledge, and IT experience are essential for accounting graduates. This finding may be used as a basic guideline to enhance IT skills and competencies for accounting graduates, by incorporating these IT elements into specific accounting degree program courses. With this, it is hoped that the supply of future accountants by educational institutions is of high quality as expected by the industry.